Art therapy: an alternative to Seniors in Costa Rica - Rodríguez Barquero, Vivian (2011)
This article is a product of a study realized with elderly people of two diurnal centers, as result of the Mastery in Sciences of the Human Movement of the University of Costa Rica. The research involved a corporal expression program carried out for five weeks, with a frequency of three times per week and a duration for session of sixty minutes. The dependent variables measured were self-esteem, short-term memory, reaction time, mood states and the quality of life of participants. The results showed important information about the benefits of the corporal expression as a very valuable initiative for the development of physical, cognitive and psychological capacities, to be a choice of creative and comprehensive physical activity and, therefore, can impact in the quality of life of the individual practitioner.